Sweden : Financial Sector Assessment Program-Technical Note-Crisis Readiness, Management, and Resolution. (IMF Staff Country Reports; Country Report ;, 2017)
This Technical Note discusses the findings and recommendations in the Financial Sector Assessment Program (FSAP) for Sweden in the areas of financial safety net and crisis management arrangements. Since the 2011 FSAP, Sweden's financial safety net and crisis management frameworks, including bank resolution and contingency planning, have improved. In response to the FSAP and the overhaul of pertinent EU rules, Sweden has enacted a host of new legislation, introduced a resolution regime for credit institutions and certain investment firms, and revised its deposit insurance system, allowing it to fund resolution measures. To ensure operational capacity to rapidly deploy recovery and resolution tools, further investments are needed to strengthen the safety net and crisis management frameworks.